Epstein–Barr virus-induced gene 3 commits human mesenchymal stem cells to differentiate into chondrocytes via endoplasmic reticulum stress sensor - Zhang, Tong; Yamagata, Kaoru; Iwata, Shigeru; Sonomoto, Koshiro; Trimova, Gulzhan; Nguyen, Anh Phuong; Hao, He; Shan, Yu; Nguyen, Mai-Phuong; Nakayamada, Shingo; Tanaka, Yoshiya (PloS one, 2022)
Mesenchymal stem cells (MSC) can differentiate into chondrocytes. Epstein–Barr virus-induced gene 3 (EBI3) is differentially expressed during chondrogenic differentiation and can be produced by MSC. EBI3 is also a subunit of interleukin (IL)-27 and IL-35, and it accumulates in the endoplasmic reticulum (ER) when its partners, such as IL-27 p28 and IL-35 p35, are insufficient. ER stress induced by protein accumulation is responsible for chondrogenic differentiation. However, the role of EBI3 and its relevance to the ER stress in chondrogenic differentiation of MSC have never been addressed. Here, we demonstrate that EBI3 protein is expressed in the early stage of chondrogenic differentiation of MSC. Additionally, knockdown, overexpression, or induction of EBI3 through IL-1β inhibits chondrogenesis. We show that EBI3 localizes and accumulates in the ER of MSC after overexpression or induction by IL-1β and TNF-α, whereas ER stress inhibitor 4-phenylbutyric acid decreases its accumulation in MSC. Moreover, EBI3 modulates ER stress sensor inositol-requiring enzyme 1 α (IRE1α) after induced by IL-1β, and MSC-like cells coexpress EBI3 and IRE1α in rheumatoid arthritis (RA) synovial tissue. Altogether, these data demonstrate that intracellular EBI3 commits to chondrogenic differentiation by regulating ER stress sensor IRE1α.